Policy Response to Substance Abuse in Selected Higher and Tertiary Education Institutions: A Comparative Review - Mweene , Daphne Lweendo; Mwale, Ganizani; Mwanza , Nicholas; Mwale, Mukonkola Machula; Makashi, Musenge (Journal of Health Policy and Management, 2025)
Background: Substance abuse in Higher and Tertiary Education Institutions (HTEIs) poses a serious threat to students’ academic achievement, mental well-being, and campus safety. Although various interventions have been introduced, the effectiveness of existing policies remains inconsistent. This study compared global literature on school-related substance abuse policies with policy responses in selected Copperbelt HTEIs in Zambia to inform the development of contextually appropriate strategies for substance abuse reduction. Subjects and Method: The study applied the Protocol, Search, Appraisal, Synthesis, and Reporting (PSALAR) framework, guided by the Population, Interest, and Context (PICo) approach. Two colleges and one university in Zambia’s Copperbelt Province were purposively selected, and an exhaustive online search was conducted to identify institutional policies addressing substance abuse. Peer-reviewed English articles (2013–2023) focusing on punitive and remedial school-based policies were reviewed. Inclusion criteria for HTEIs were adapted to align with the PSALAR framework. Results: Three major themes emerged: (1) policy deficiencies and implementation gaps, (2) punitive versus remedial interventions, and (3) limited monitoring and evaluation mechanisms. The dominant issue was finding an effective balance between punitive and supportive policy approaches. The integration of substance abuse education within institutional frameworks was weak, and evidence on the relative effectiveness of punitive versus remedial measures remained inconclusive. Conclusion: Substance abuse policies in Zambian HTEIs predominantly emphasize punitive responses, with insufficient attention to remedial or preventive efforts. Strengthening evidence-based, context-specific, and student-centered policies is essential to reduce substance abuse and advance Zambia’s progress toward Sustainable Development Goal 3.5 by 2030.